2022
DOI: 10.3390/condmat7040070
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Trends in Hybrid-DFT Computations of BaTiO3/SrTiO3, PbTiO3/SrTiO3 and PbZrO3/SrZrO3 (001) Hetero Structures

Abstract: We performed predictive hybrid-DFT computations for PbTiO3, BaTiO3, SrTiO3, PbZrO3 and SrZrO3 (001) surfaces, as well as their BaTiO3/SrTiO3, PbTiO3/SrTiO3 and PbZrO3/SrZrO3 (001) heterostructures. According to our hybrid-DFT computations for BO2 and AO-terminated ABO3 solid (001) surfaces, in most cases, the upper layer ions relax inwards, whereas the second layer ions shift upwards. Our hybrid-DFT computed surface rumpling s for the BO2-terminated ABO3 perovskite (001) surfaces almost always is positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 138 publications
0
3
0
Order By: Relevance
“…According to our ab initio B3PW computations, the largest chemical bond populations are between the Ti and O atoms (0.100e) in the BTO perovskite and between the Zr and O atoms (0.100e) in the PZO perovskite (Table 4). We carried out ab initio B3PW computations of the STO/BTO (001) heterostructures [77,91] by means of the symmetrically terminated slab model (Figure 1). The TiO2-terminated STO (001) substrate contained eleven atomic monolayers (Figure 1).…”
Section: Ab Initio B3pw-computed Abo 3 Perovskite Bulk Propertiesmentioning
confidence: 99%
“…According to our ab initio B3PW computations, the largest chemical bond populations are between the Ti and O atoms (0.100e) in the BTO perovskite and between the Zr and O atoms (0.100e) in the PZO perovskite (Table 4). We carried out ab initio B3PW computations of the STO/BTO (001) heterostructures [77,91] by means of the symmetrically terminated slab model (Figure 1). The TiO2-terminated STO (001) substrate contained eleven atomic monolayers (Figure 1).…”
Section: Ab Initio B3pw-computed Abo 3 Perovskite Bulk Propertiesmentioning
confidence: 99%
“…On the other hand, the Hartree-Fock (HF) method tends to overestimate the bandgaps. However, recent theoretical studies have suggested that by utilizing the B3LYP or B3PW functionals, it is possible to achieve excellent agreement between the calculated band gaps and experimental data for ABO 3 perovskites [37,38]. For the phonon spectra calculation, the density-functional-perturbation theory (DFPT) was used and 5 × 5 × 1 supercell of C 3 P, C 3 N and C 6 NP was adopted [39].…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that modified Becke and Johnson (mBJ) exchange-correlation potential and hybrid exchangecorrelation functionals such as B3LYP or B3PW have demonstrated the capability to achieve excellent agreement with experimental band gap values for ABO 3 perovskite materials. 29,30 In contrast, GGA descriptions of exchange and correlation effects often result in an underestimation of the band gap. To address this band gap underestimation, we have employed the mBJ exchange-correlation potential to enhance the accuracy of our electronic band gap calculations for the studied materials.…”
Section: Computational Model and Detailsmentioning
confidence: 99%
“…As for this work, one has used the generalized gradient approximation (GGA) 28 under the effects of spin polarization considering the following formula. EitalicXCitalicGGAnn=d3rfnnnn, where n and n are the number of electrons in spin‐down and spin‐up configuration, respectively. It is reported that modified Becke and Johnson (mBJ) exchange‐correlation potential and hybrid exchange‐correlation functionals such as B3LYP or B3PW have demonstrated the capability to achieve excellent agreement with experimental band gap values for ABO 3 perovskite materials 29,30 . In contrast, GGA descriptions of exchange and correlation effects often result in an underestimation of the band gap.…”
Section: Computational Model and Detailsmentioning
confidence: 99%